Using Evidence to End Homelessness - Teixeira, Lígia; Cartwright, James (Policy Press, 2020)
Available open access under CC-BY-NC license. The Centre for Homelessness Impact brings together this urgent book gathering the insights of leaders in government, academia and the third sector to present new evidence-based strategies to end homelessness. Contributors advocate for a new movement that embraces data and evidence to end homelessness effectively, providing crucial methods to underpin future policy, practice and funding decisions.